Etoricoxib-Loaded Transdermal Patches with Thiolated Pyrimidin Chitosan for Enhanced Delivery - Raza, Sajid; Khan, Waqas Ahmad; Khan, Nasir; Mahmood, Saima; Ahmad, Afzaal; Khan, Shadman; Ilyas, Yusra; Kainat, Hafiza Asma; Bin Khalid, Rizwan Ullah (Indus Journal of Bioscience Research, 2025)
This study focused on the development and evaluation of etoricoxib-loaded transdermal patches for sustained drug delivery to enhance bioavailability and patient compliance. The patches were formulated using polymeric matrices to achieve controlled drug release and improved skin permeability. Various physicochemical characterizations, including surface morphology, thickness, weight uniformity, folding endurance, tensile strength, and moisture content, were conducted to ensure uniformity and mechanical stability. In vitro drug release studies demonstrated a sustained release profile over 24 hours, preventing burst release while maintaining therapeutic drug levels. Ex vivo permeation studies using Wistar rat skin confirmed efficient drug penetration, enhanced by penetration enhancers. A six-month accelerated stability study (40°C ± 2°C, 75% ± 5% RH) showed no significant changes in drug content or release profile. The optimized formulation (F6) exhibited superior mechanical properties, enhanced skin permeation, and controlled drug release, making it a promising alternative to oral etoricoxib for long-term pain management and anti-inflammatory therapy.